A Minor Subpopulation of Mycobacteria Inherently Produces High Levels of Reactive Oxygen Species That Generate Antibiotic Resisters at High Frequency From Itself and Enhance Resister Generation From Its Major Kin Subpopulation - Nair, Rashmi Ravindran; Sharan, Deepti; Ajitkumar, Parthasarathi (Frontiers in Microbiology, 2019)
Antibiotic-exposed bacteria produce elevated levels of reactive oxygen species (ROS), to which either they succumb or get mutated genome-wide to generate antibiotic resisters. We recently showed that mycobacterial cultures contained two subpopulations, short-sized cells (SCs; ~10%) and normal/long-sized cells (NCs; ~90%). The SCs were significantly more antibiotic-susceptible than the NCs. It implied that the SCs might naturally be predisposed to generate significantly higher levels of ROS than the NCs. This in turn could make the SCs more susceptible to antibiotics or generate more resisters as compared to the NCs. Investigation into this possibility showed that the SCs in the actively growing mid-log phase culture naturally generated significantly high levels of superoxide, as compared to the equivalent NCs, due to the naturally high expression of a specific NADH oxidase in the SCs. This caused labile Fe2+ leaching from 4Fe-4S proteins and elevated H2O2 formation through superoxide dismutation. Thus, the SCs of both Mycobacterium smegmatis and Mycobacterium tuberculosis inherently contained significantly higher levels of H2O2 and labile Fe2+ than the NCs. This in turn produced significantly higher levels of hydroxyl radical through Fenton reaction, promoting enhanced antibiotic resister generation from the SCs than from the NCs. The SCs, when mixed back with the NCs at their natural proportion in the actively growing mid-log phase culture, enhanced antibiotic resister generation from the NCs, to a level equivalent to that from the unfractionated whole culture. The enhanced antibiotic resister generation from the NCs in the reconstituted SCs-NCs natural mixture was found to be due to the high levels of H2O2 secreted by the SCs. Thus, the present work unveils and documents the metabolic designs of two mycobacterial subpopulations where one subpopulation produces high ROS levels, despite higher susceptibility, to generate significantly higher number of antibiotic resisters from itself and to enhance resister generation from its kin subpopulation. These findings show the existence of an inherent natural mechanism in both the non-pathogenic and pathogenic mycobacteria to generate antibiotic resisters. The presence of the SCs and the NCs in the pulmonary tuberculosis patients’ sputum, reported by us earlier, alludes to the clinical significance of the study.